Migration and Emotional Distress Among Left-Behind Wives in Rural Nepal - Kurmi, Balawant (Chhahari छहारी, 2026)
Male labor migration from rural Nepal has become a defining socio-economic phenomenon that simultaneously promotes household prosperity and disrupts family structures. While remittances enhance financial security, the emotional cost borne by wives left behind remains profound yet under-researched. This study investigates the psychosocial and emotional distress experienced by left-behind wives in rural Nepal, exploring the interplay between patriarchal norms, socio-cultural pressures, economic dependencies, and limited access to mental health support. Drawing on a synthesis of recent empirical and theoretical studies from 2010–2025, the research reveals that prolonged spousal separation contributes to chronic loneliness, anxiety, and depression among women, exacerbated by increased domestic burdens and societal stigma. Consistent remittance flow and frequent communication with migrant husbands serve as partial buffers, though they rarely mitigate the deeper emotional void or social isolation. The review identifies remittance reliability, communication frequency, and community support as key mediators of psychosocial well-being. Findings further highlight that while migration-induced role shifts can increase women’s autonomy in financial and household decision-making, they also intensify workloads and emotional exhaustion. The study concludes that sustainable interventions must integrate mental health services with gender-sensitive development and empowerment initiatives. Policies focusing solely on economic remittances fail to address the complex emotional dimensions of migration. A holistic, multi-sectoral approach-combining psychosocial counseling, community awareness, and digital connectivity-can enhance resilience and ensure the well-being of left-behind wives, thereby promoting both family and national development.